Delaying reverse transcription does not increase sensitivity of HIV-1 to human TRIM5α. - Emilie Battivelli (Public Library of Science (PLoS), 2013)
Background Because uncoating of the capsid is linked to reverse transcription, modifications that delay this process lead to the persistence in the cytoplasm of capsids susceptible to recognition by the human restriction factor TRIM5α (hTRIM5α). It is unknown, however, if increasing the time available for capsid-hTRIM5α interactions would actually render viruses more sensitive to hTRIM5α. Results Viral sensitivity to hTRIM5α was evaluated by comparing their replication in human U373-X4 cells in which hTRIM5α activity had or had not been inhibited by overexpression of human TRIM5γ. No differences were observed comparing wild-type HIV-1 and variants carrying mutations in reverse transcriptase or the central polypurine tract that delayed the completion of reverse transcription. In addition, the effect of delaying the onset of reverse transcription for several hours by treating target cells with nevirapine was evaluated using viral isolates with different sensitivities to hTRIM5α. Delaying reverse transcription led to a time-dependent loss in viral infectivity that was increased by inhibiting capsid-cyclophilin A interactions, but did not result in increased viral sensitivity to hTRIM5α, regardless of their intrinsic sensitivity to this restriction factor. Conclusions Consistent with prior studies, the HIV-1 capsid can be targeted for destruction by hTRIM5α, but different strains display considerable variability in their sensitivity to this restriction factor. Capsids can also be lost more slowly through a TRIM5α-independent process that is accelerated when capsid-cyclophilin A interactions are inhibited, an effect that may reflect changes in the intrinsic stability of the capsid. Blocking the onset or delaying reverse transcription does not, however, increase viral sensitivity to hTRIM5α, indicating that the recognition of the capsids by hTRIM5α is completed rapidly following entry into the cytoplasm, as previously observed for the simian restriction factors TRIM-Cyp and rhesus TRIM5α.